Late Pleistocene owls (Aves, Strigiformes) from Ecuador, with the description of a new species - Lo Coco, Gastón Ernesto (2020)
The fossil record of owls of the families Strigidae and Tytonidae in South America is poor. The aim of the present contribution is to report for the first time fossil Strigiformes from Riobamba Canton, at Chimborazo province, in Ecuador. The specimens come from a large owl burrow from Late Pleistocene beds of the Cangagua Formation. We report the finding of fossil record of Athene cunicularia and Tyto aff. T. furcata and the first fossil record of Glaucidium from Ecuador. Further, a giant species of the genus Asio is described. The specimen constitutes the largest known asionine owl, being approximately of the size of a big female of Bubo virginianus. Based on prey content at the fossil burrow, it is possible that the new Asio species predated on the other owls. If this inference is correct, it may represent the first evidence indicating intra-ordinal predation in the fossil record.